2017
DOI: 10.1007/s11255-017-1624-9
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, muscular cramps and pruritus have low intensity in hemodialysis patients with good dialysis efficiency, low inflammation and arteriovenous fistula

Abstract: HD patients with AVF have less insomnia, muscular cramps and pruritus. Insomnia is associated with muscular cramps and inflammation. Pruritus is worse in older patients, is diminished with increased dialysis efficiency and is associated with higher CRP in men. There is no difference between HD and HDF patients, except more severe insomnia for HD in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
3
5
1
Order By: Relevance
“…In accordance with previous studies, recovery time was unrelated to age [7,9] and some clinical variables such as the Charlson comorbidity index [7] and insomnia [36].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies, recovery time was unrelated to age [7,9] and some clinical variables such as the Charlson comorbidity index [7] and insomnia [36].…”
Section: Discussionsupporting
confidence: 91%
“…Pruritus and insomnia are common disorders in hemodialysis (HD) patients. Pruritus affects up to 40% of end-stage renal disease (ESRD) patients and has a major clinical impact, being associated strongly with poor quality of life, impaired sleep, depression, and increased mortality [1,2]. Sleep disorders are experienced by approximately 50-75% of ESRD patients [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus affects up to 40% of end-stage renal disease (ESRD) patients and has a major clinical impact, being associated strongly with poor quality of life, impaired sleep, depression, and increased mortality [1,2]. Sleep disorders are experienced by approximately 50-75% of ESRD patients [2][3][4]. Insomnia reduces overall quality of life and may lead to other complications including impaired immune system and risk for cardio- vascular disease [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have linked various aspects of the dialysis prescription with intra-dialytic and post-dialysis symptom reporting, including the choice of dialysate sodium, potassium and temperature [7][8][9]. Whereas others have reported that the prevalence of intra-dialysis symptoms and post-dialysis fatigue is reduced by achieving greater urea clearance [10], or by changing from the standard thrice weekly dialysis schedule to shorter but more frequent daily dialysis sessions [11], or low-efficiency continuous dialysis [12]. Whether adding convective clearance or switching from haemodialysis to haemofiltration improves intra-dialytic symptoms and post-dialysis recovery times remains unclear, with some studies reporting a benefit and others no effect [9,12,13].…”
Section: Introductionmentioning
confidence: 99%